The lagged effect of cold temperature and wind chill on cardiorespiratory mortality in Scotland. Issue 10 (16th September 2005) - Carder, M; McNamee, R; Beverland, I; Elton, R; Cohen, G R; Boyd, J; Agius, R M
Abstract : Aims: To investigate the lagged effects of cold temperature on cardiorespiratory mortality and to determine whether "wind chill" is a better predictor of these effects than "dry bulb" temperature. Methods: Generalised linear Poisson regression models were used to investigate the relation between mortality and "dry bulb" and "wind chill" temperatures in the three largest Scottish cities (Glasgow, Edinburgh, and Aberdeen) between January 1981 and December 2001. Effects of temperature on mortality (lags up to one month) were quantified. Analyses were conducted for the whole year and by season (cool and warm seasons). Main results: Temperature was a significant predictor of mortality with the strongest association observed between temperature and respiratory mortality. There was a non-linear association between mortality and temperature. Mortality increased as temperatures fell throughout the range, but the rate of increase was steeper at temperatures below 11°C. The association between temperature and mortality persisted at lag periods beyond two weeks but the effect size generally decreased with increasing lag. For temperatures below 11°C, a 1°C drop in the daytime mean temperature on any one day was associated with an increase in mortality of 2.9% (95% CI 2.5 to 3.4), 3.4% (95% CI 2.6 to 4.1), 4.8% (95% CI 3.5 to 6.2) and 1.7% (95% CI 1.0 to 2.4) over the following month for all cause, cardiovascular, respiratory, and "other" cause mortality respectively. The effect of temperature on mortality was not observed to be significantly modified by season. There was little indication that "wind chill" temperature was a better predictor of mortality than "dry bulb" temperature. Conclusions: Exposure to cold temperature is an important public health problem in Scotland, particularly for those dying from respiratory disease.